MEMBANGUN JARINGAN KOMPUTER NIRKABEL DENGAN PENGOPERASIAN SISTEM OPERASI UNIX DENGAN IMPLEMENTASI IPV6 PADA FREEBSD - BERTHA MEYKE WATY HUTAJULU (Faktor Exacta, 2015)
Wireless network is a quite new technology in computer network world. It can connect computers without any wireless, but it use radio frequency at 2.4 GHz. For computer network still use wire to connected computers. Wireless is use the air medium, so there is different medium between wire and air. To connect these two medium networks we need other hardware. The hardware is called access point, but there is other problem comes. Access point price is quite expensive, so to handle this problem people were tried to look for another alternative. The alternative is use a personal computer with FreeBSD operating system. Operating system UNIX FreeBSD is a computer software that manage and control the operation of computer system based on UNIX. Free is defined as free software, or can be used as desired by users. While the BSD (Barkeley Software Distribution) is a development of the UNIX source code that to create as operating system portable, multi-tasking, multi-user, hierarkis system and utility. As utility Unix C-Shell, VI, TCP/IP and memory virtual, to created for build a stable FreeBSD. In its development, UNIX FreeBSD also effectthe development of UNIX systems that exist. As basic utilities Unix C-Shell, VI, TCP/IP and virtual memory, example httpd-2.0, thttpd, exim, courier-imap, was created to be able to adjust to the BSD features. FreeBSD operating system support dual stack (IPv4 and IPv6). IPv6 stack is installed by default on FreeBSD operating system. Besides the basic application FreeBSD also supports IPv6 which can be installed trough port mechanisme. FreeBSD is believed to be operating system for serves that handle high loads. At the time, recorded some of the worlds busiest internet sites such as yahoo.com, hotmail.com, ftp.cdrom.com for use. But it can't simulate access point perfectly because access point is hardware. It doesn't matter that can't simulate perfectly because not all feature that access point have are use. Keyword: Operating System Unix FreeBSD, wireless LAN, computer network